PENGUJIAN PENCEMARAN DAGING BABI PADA BEBERAPA PRODUK BAKSO DENGAN TEKNOLOGI PCR: PENCARIAN SISTEM PENGUJIAN EFEKTIF - Endang Tri Margawati; Muhamad Ridwan (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Entering globalization market, Indonesian government could not reject any import of food products from overseas. To anticipate the possibility of porcine contaminants into processed meat products of imported food such as meat or chicken ball, sausage, tin meat etc., it is important to apply laboratory research on such particular matter in regard to ethical and certain religious concern. This study was intended to identify the possibility of porcine contaminants into either processed meat products or fresh meat.A technique of polymerase chain reaction (PCR) was applied and PCR optimizing was conducted in advanced to obtain the right annealing temperature.Positive control of fresh pork meat was amplified to get porcine Leptin size which is 152bp fragment. Five samples of 4 meat balls and one fresh beef meat were individually collected for their DNA by either from minced or mashed after liquid nitrogen exposure then followed with a series of DNA extraction steps. PCR was assigned by using a specific primer of Leptin gene for porcine identification.Visualization of Leptin fragment was applied either on 1%, 2% of agarose gel or 10-20% gradient acrylamide gel.The result showed that all sample applied were not identified for containing porcine contaminants while positive control was on the right size of 152bp of Leptin gene. Specific primer used in this study was proved that there was not identified porcine Leptin gene on the negative control (fresh beef meat). This study suggests that a method of PCR is a simple analytical method for identification of porcine contaminants and visualization on 2% agarose gel is a cheaper and quicker method while by gradient acrylamide gel showing more clear band however this method is time consuming and expensive.